COMPARATIVE PETROGRAPHY OF OMBILIN AND BAYAH COALS RELATED TO THEIR ORIGIN - BINARKO SANTOSO; BUKIN DAULAY (Puslitbang tekMIRA, 2007)
Two coalfields have been contrasted and compared on the basis of qualitative and quantitative stud- ies of macerals and minerals. Petrological comparison of the coals indicates that vitrinite and liptinite contents within Ombilin coal are higher than those of the Bayah coal. The inertinite content of both coals is somewhat similar. Mineral matter of Bayah coal is higher than that of Ombilin coal. The vitrinite reflectance and rank of the Ombilin coal is higher and thus, its coal rank (sub-bituminous to anthracite) is better than that of the Bayah coal (sub-bituminous to medium volatile bituminous). A clear distinction between the Ombilin and Bayah coals is not possible with petrographic methods alone, and other geological parameters have to be considered. The maceral compositions of the Ombilin and Bayah coals are slightly different from each other due to intrusion effect. In the thermally affected coals from both areas, liptinite generally cannot be distinguished from vitrinite and therefore it appears to contain high proportion of vitrinite (>90 %). However, thermally unaffected coals from both coalfields contain <90 % of vitrinite. Liptinite maceral is common in coals unaffected by contact alteration with some samples containing up to 10 %. In contrast, thermally affected coals have trace amounts of liptinite. Both thermally affected and affected coals contain rare inertinite with some samples containing up to 7 %. In some cases, coals with high inertinite content have a relatively high amount of mineral matter. The Ombilin and Bayah coals show variable vitrinite reflectances, due to igneous intrusion factor. Coal of lower rank has been metamorphosed to bituminous or anthracitic ranks. The extent of rank increase depends primarily on distance from the intruding igneous rock, but it may also be related to size and temperature of the intrusion. As the vitrinite reflectance (Rvmax) values of the Ombilin coal (0.62-4.69 %) are higher compared to the Bayah coal (0.53-1.23 %), this suggests that the heat source to the thermally affected coals is closer in the Ombilin coal than that of in the Bayah coal.